The Importance of Al-’Ilm in Smart Society 5.0 Era: Reviews from The Qur’an and Hadith: Pentingnya Ilmu di Era Masyarakat Cerdas 5.0: Tinjauan Al-Qur’an dan Hadis - Ida Fitri Anggarini; Edy Kurniawan; Moh. Ali Ridho; Suci Wulandari; M. Iqbal; Liska Lestari (STAI Ma'had Aly Al-Hikam Malang, 2023)
Smart Society 5.0 Era is a new thing that contains good and bad impacts. The focus of this Era is to promote human resources. This research aims to analyze and roll out the urgency of science in the Smart Society 5.0 Era. This qualitative literature study was used to collect data and analyze the urgency of science by Al-Qur’an and Hadith. This research finds out that even all the chapters of the Al-Qur’an contain any educational meaning, but the researcher focuses on: 1) Surah al-Baqarah: 31; 2) Surah al Mujadalah:11; 3) Hadith narrated by al-Bukhari; 4) Hadith narrated by Ibn Majah. The conclusion is: 1) Smart Society 5.0 Era as the urgency of al-’ilm implication; 2) As Muslims must be well prepared and able to face any challenges and look for opportunities in this era; 3) A lot of silver linings in Al-Qur’an and Hadith as motivation to face this era. 4) Exploring talent to find out the urgency of science and reach glory through science. Kata Kunci: Al-’Ilm, Al-Qur’an, Hadith, Smart Society 5.0.